Analisis persepsi dan permasalahan yang dihadapi guru dalam penerapan ability grouping di sekolah dasar - Nurul Hidayatun Nafiah; Hadi Mulyono; Fadhil Purnama Adi (Didaktika Dwija Indria, 2022)
Several educational institution implement ability grouping to grouping students. However, the reality in the field shows that the ability grouping still raises several pros and cons. This research was conducted with the aim of knowing the perceptions and problems faced by teachers in the application of ability grouping. This research is qualitative study. The subjects of this study were teachers at MI Baitussalam Gadingan, Mojolaban, Sukoharjo. Data was collected using interviews, open questionnaires and documentation. The results of this study indicate that there are differences in perceptions between the teacher groups of students A and B. The group A teacher considers the application of ability grouping to be able to facilitate teachers and students in implementing learning, while the group B teachers think that the application of ability grouping is not enough to facilitate the teacher in carrying out learning in class. The problems faced in the application of ability grouping were mostly experienced by group B teachers.